2017
DOI: 10.1093/cid/ciw778
|View full text |Cite
|
Sign up to set email alerts
|

Official American Thoracic Society/Infectious Diseases Society of America/Centers for Disease Control and Prevention Clinical Practice Guidelines: Diagnosis of Tuberculosis in Adults and Children

Abstract: Background Individuals infected with Mycobacterium tuberculosis (Mtb) may develop symptoms and signs of disease (tuberculosis disease) or may have no clinical evidence of disease (latent tuberculosis infection [LTBI]). Tuberculosis disease is a leading cause of infectious disease morbidity and mortality worldwide, yet many questions related to its diagnosis remain. Methods A task force supported by the American Thoracic Society, Centers for Disease Control and Prevention, and Infectious Diseases Society of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
452
0
29

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(490 citation statements)
references
References 0 publications
9
452
0
29
Order By: Relevance
“…66 Sputum induction is more cost effective than bronchoscopic examination and should be the test of choice if smear-negative pulmonary TB is the most likely diagnosis. 66,67 Chew et al have demonstrated that, in an intermediate burden setting where clinicians may be reluctant to start expectant treatment, the testing of Xpert MTB/RIF assay can help facilitate diagnostic yield and early treatment decisions in patients with pulmonary TB. 68 We must also consider that in certain settings, it is common to lack access to high-quality chest roentgenograms and people who can reliably interpret them, and there may not be access to the Xpert MTB/RIF assay.…”
Section: Tuberculosismentioning
confidence: 99%
“…66 Sputum induction is more cost effective than bronchoscopic examination and should be the test of choice if smear-negative pulmonary TB is the most likely diagnosis. 66,67 Chew et al have demonstrated that, in an intermediate burden setting where clinicians may be reluctant to start expectant treatment, the testing of Xpert MTB/RIF assay can help facilitate diagnostic yield and early treatment decisions in patients with pulmonary TB. 68 We must also consider that in certain settings, it is common to lack access to high-quality chest roentgenograms and people who can reliably interpret them, and there may not be access to the Xpert MTB/RIF assay.…”
Section: Tuberculosismentioning
confidence: 99%
“…These results also provide another demonstration of the potential pitfalls of serial TB screening in a low-risk population. When the prevalence of a disease in the population is low (e.g., <1%) and the performance characteristics of screening tests are poor, 4 most positive tests are falsely positive. 3,10 Annual TB screening programs should be modified to eliminate automatic annual LTBI testing for low-risk, previously negative HCWs and could instead be structured to carefully evaluate individual exposure risks and personal health history.…”
Section: Discussionmentioning
confidence: 99%
“…4 Additionally, any HCWs exposed to a patient with pulmonary TB prior to the institution of airborne precautions are evaluated with a postexposure TST. 4 All positive TST results are followed up with a clinical exam and chest radio-graph to evaluate for active TB disease.…”
Section: Methodsmentioning
confidence: 99%
“…According to international guidelines (Lewinsohn et al, 2017), there are insufficient data to recommend a preference for either a TST or an IGRA as the first-line diagnostic test in immunocompromised patients: it has been suggested that a combined TST-IGRA test is probably the best way to improve sensitivity, particularly when the consequences of missing a case of LTBI exceed the risk of adverse events related to the treatment, mostly liver toxicity (Anibarro & Pena, 2014;Lewinsohn et al, 2017).…”
Section: Clinical Scenario 3 Tuberculosis Reactivation Riskmentioning
confidence: 99%